A Multiparametric Approach to Unravelling the Geoenvironmental Conditions in Sediments of Bay of Koper (NE Adriatic Sea): Indicators of Benthic Foraminifera and Geochemistry - Žvab Rožič, Petra; Vidović, Jelena; Ćosović, Vlasta; Hlebec, Ana; Rožič, Boštjan; Dolenec, Matej (Frontiers in Marine Science, 2022)
The Bay of Koper is influenced by agricultural, urban, and port activities, therefore pollution from trace metals is a concern. A total of 20 sediment samples obtained from four 10-cm sediment cores were analyzed. Element concentration in the sediment of the bay was determined spatially and temporally from the recent surface to depth. The results were correlated with the composition and diversity of the benthic foraminiferal assemblages. Major element concentrations indicate natural lithogenic origin (which is also confirmed by mineralogical features). The benthic foraminiferal assemblages in sediment samples, although mainly composed of representatives of the Rotaliida, show moderate to high species diversity and are dominated by the pollution tolerant species Ammonia pakinsoniana, Haynesina sp., Valvulineria bradyana and the non-keel Elphidium sp. and subordinated by Ammonia tepida and Haynesina depressula. Canonical correspondence analysis (CCA) on foraminiferal species and trace element concentrations shows a possible control of some potential toxic elements (i.e., Cu, Ni, Pb, Zr, Cr, As) on the diversity and taxonomic composition of foraminiferal assemblages. Nevertheless, foraminiferal diversity and dominance in the bay are related to sediment characteristics such as sediment grain size, and the amount of terrigenous inflow rather than to the element concentrations of sediments. This study evaluated ecological conditions by using the Foram-AMBi and EcoQS indices. The values of the Foram-AMBI index reflect the good to moderate quality of ecological conditions, whereas high to poor ecological statuses were interpreted by calculating EcoQS.